2014
DOI: 10.1002/cncr.28600
|View full text |Cite
|
Sign up to set email alerts
|

National trends in prostate cancer screening among older American men with limited 9‐year life expectancies: Evidence of an increased need for shared decision making

Abstract: BACKGROUND: Prostate-specific antigen (PSA) screening for prostate cancer remains controversial. Most groups recommend informed decision making for men with 10 years of remaining life expectancy. The primary objective of this observational cohort study was to investigate the association between predicted 9-year mortality and prostate cancer screening among American men aged 65 years in 2005 and 2010. The second objective was to analyze the proportions of men who discussed screening with their physicians. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 21 publications
2
55
0
Order By: Relevance
“…Surprisingly, more than 30% of patients treated with anticholinesterase therapies and 20% of patients with six or more ambulance transportations during the study period underwent a PSA-based prostate screening. While all the guidelines recommend avoiding screening in patients with a life expectancy of less than 10 years [8] [18] [34][35], previous authors have also reported inappropriate screening practices in vulnerable patients [36][37][38]. These results emphasize that integrating life expectancy into medical decisions remains a challenge for primary care physicians [39][40].…”
Section: Discussionsupporting
confidence: 51%
“…Surprisingly, more than 30% of patients treated with anticholinesterase therapies and 20% of patients with six or more ambulance transportations during the study period underwent a PSA-based prostate screening. While all the guidelines recommend avoiding screening in patients with a life expectancy of less than 10 years [8] [18] [34][35], previous authors have also reported inappropriate screening practices in vulnerable patients [36][37][38]. These results emphasize that integrating life expectancy into medical decisions remains a challenge for primary care physicians [39][40].…”
Section: Discussionsupporting
confidence: 51%
“…24,25 Conversely, approximately 45% of men in their 70s undergo PSA based screening, even those at high risk for other cause mortality, exposing these patients to the risks of detection and treatment without measurable survival benefit. 26 …”
Section: Screening Detection and Over Treatment Of Gleason 6 Prostatmentioning
confidence: 99%
“…42 Large numbers of older men undergo PSA screening with a low likelihood of benefit 26 and determining who can safely stop screening is important. Among a large cohort of men from Sweden it has been demonstrated that men with a PSA less than 1 ng/ml at age 60 have a risk of prostate cancer death by age 85 of 0.2%.…”
Section: The Way Forward: Improved Risk Stratification and Active Surmentioning
confidence: 99%
“…In addition, the authors conclude that the current UK policy allowing all men to make an informed choice about PSA testing is not being effectively implemented [9]. In the USA, approximately 33% of older men with a high likelihood of 9-yr mortality are screened despite minimal clinical benefit [10]. Data on PSAtriggered prostate biopsy and repeat biopsy (after an initial negative biopsy) are also discouraging, with positive predictive values of 12-50% and many men undergoing repeated biopsy.…”
mentioning
confidence: 89%